Comparative Extraction of Aluminum Group Metals Using Acetic Acid Derivatives with Three Different-Sized Frameworks for Coordination - Keisuke Ohto (MDPI AG, 2021)
We prepared acetic acid derivatives using three different frameworks, calix[4]arene, alkenyltrimethylol, and trihydroxytriphenylmethane, which differ in the number and size of their coordination sites. We further investigated the extraction properties for aluminum group metal ions. All three extraction reagents exhibited increased extraction compared with the corresponding monomeric compounds, owing to structural effects. The extraction reaction and extraction equilibrium constants were determined using a slope analysis. Their extraction abilities, separation efficiencies, and potential coordination modes are discussed using the extraction equilibrium constants, half-pH values, and spectroscopic data. The calix[4]arene and trihydroxytriphenylmethane derivatives demonstrated allosteric co-extraction of indium ions (In3+) with an unexpected stoichiometry of 1:2.